2002
DOI: 10.2134/jeq2002.1980
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal and Nitrate Leaching for Forage Systems Receiving Dairy Effluent

Abstract: Florida dairies need year-round forage systems that prevent loss of N to ground water from waste effluent sprayfields. Our purpose was to quantify forage N removal and monitor nitrate N (NO3(-)-N) concentrations in soil water below the rooting zone for two forage systems during four 12-mo cycles (1996-2000). Soil in the sprayfield is an excessively drained Kershaw sand (thermic, uncoated Typic Quartzipsamment). Over four cycles, average loading rates of effluent N were 500, 690, and 910 kg ha(-1) per cycle. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Dairy farmers, on the other hand, may find this management change infeasible because they need to maintain certain milk production levels that they think can only be reached with high protein levels. Another example is a researcher's recommendation based on model outcomes, to plant Bermudagrass in lieu of another species (Woodard et al, 2002). A dairy farmer might recognize the change as good for reducing N leaching, but may not be able to make the change because it is economically or financially infeasible.…”
Section: Comparing Scientists and Dairy Farmers' Perceptions On Climamentioning
confidence: 99%
See 2 more Smart Citations
“…Dairy farmers, on the other hand, may find this management change infeasible because they need to maintain certain milk production levels that they think can only be reached with high protein levels. Another example is a researcher's recommendation based on model outcomes, to plant Bermudagrass in lieu of another species (Woodard et al, 2002). A dairy farmer might recognize the change as good for reducing N leaching, but may not be able to make the change because it is economically or financially infeasible.…”
Section: Comparing Scientists and Dairy Farmers' Perceptions On Climamentioning
confidence: 99%
“…Consequently, N leaching, the difference between N in the soil and N uptake, is also impacted by ENSO climatic changes. More specifically, N losses from forage crop rotations on a dairy farm in the study area have been shown to be influenced by inter-annual climatic variability (Woodard et al, 2002). Woodward's study lasted four years (1996)(1997)(1998)(1999), and even though it included one El Niño phase (1997)(1998), one La Niña phase (1999)(2000) and two Neutral years, it does not provide enough information to generalize results according to ENSO phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2; added N availability. Cover cropping (Jackson et al, 1993;Wyland et al, 1996;Constantin et al, 2010) and perennial grass (Woodward, 2002) also reduced the potential of nitrate leaching. Soil organic N has also been found to increase with perennial grass (Giddens et al, 1971).…”
Section: Discussionmentioning
confidence: 95%
“…Forage vegetation can substantially improve the potential of land treatment system for nutrient removal because, unlike grain production systems, nearly all aboveground biomass is removed during harvest (Paranychianakis et al, 2006;Woodard et al, 2002). For instance, 465, 528, and 585 kg N/ha per cycle were removed by a Bermuda grass-rye system for the low, medium, and high rates of dairy effluent, respectively, during a study of four 12-month cycles (Woodard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%